Method for regenerating and upgrading retired ternary lithium ion battery
By using the ternary eutectic molten salt-assisted regeneration method, the used ternary lithium-ion battery positive electrode material is converted into a new high-nickel positive electrode material, which solves the problems of low recycling efficiency, high cost and unenvironmental protection in the existing technology, and realizes the Efficient, economical and environmentally friendly regeneration upgrades, and electrochemical performance is close to commercial cathode materials.
Patent Information
- Application Number
- CN202411674261.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
When recycling waste lithium-ion battery positive electrode materials, the prior art has low separation efficiency, cumbersome processes, consumes a large amount of corrosive reagents, is high in cost and is not environmentally friendly, and the added value of traditional metallurgical recycling methods is low, which reduces the economicality of recycling.
Using the ternary eutectic molten salt-assisted regeneration method, the waste ternary lithium-ion battery is soaked in NaCl solution, separated the positive electrode sheet, rinsed, vacuum dried, separated the current collector in NaOH solution, suction filtration and washing, calcination and ball milling, etc. Convert to new high nickel cathode material.
It improves the reusability of metal elements in waste lithium-ion batteries, reduces production costs, simplifies the processing process, achieves environmentally friendly and economical regeneration upgrades, and the electrochemical performance of recycled materials is close to that of commercial cathode materials.
Smart Images

Figure CN119481404A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste battery utilization, and specifically relates to a method for regenerating and upgrading retired ternary lithium-ion batteries. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in large-scale energy storage devices and electronic devices, resulting in a rapid rise in the prices of related metal elements such as lithium, cobalt and nickel. At the same time, the resulting large amount of waste lithium-ion batteries has put tremendous pressure on the environment, and the leakage of heavy metals and organic electrolytes poses potential safety issues. It can also be expected that the demand for lithium-ion batteries will continue to grow in the future, especially under China's "dual carbon" goals of carbon peak and carbon neutrality. Among them, the ternary positive electrode material lithium nickel cobalt manganese oxide (LNCMO) has a higher specific capacity and application prospects. This type of material has been widely used in daily electronic products and electric vehicles. In order to improve the cycle stability of battery positive electrode materials, there are studies on the modification of positive electrode materials such as doping and coating. Positive electrode materials with diversified modification methods have brought great challenges to the recycling and treatment of waste lithium-ion batteries.
[0003] Traditional recycling methods for waste lithium-ion battery positive electrodes are usually divided into pyrometallurgical recycling and wet recycling. First, the lithium battery is mechanically disassembled and separated to separate the positive electrode material from the waste lithium battery. Wet recycling usually separates the current collector from the positive electrode material by acid leaching or alkaline leaching, and then recovers the precious metal ions in the positive electrode material in the form of a single substance; pyrometallurgical recycling is a method of direct calcination to decompose the binder in the positive electrode material by heat, recover the positive electrode material powder, and then use chemical means for the next step of conversion and utilization.
[0004] Through the above background analysis, it can be seen that the above recycling and treatment methods have the following problems: First, physical methods are required to separate the positive electrode materials of waste batteries from the conductive agent and the binder, which is a relatively cumbersome process and has a low separation efficiency; second, a large amount of corrosive reagents such as acids and alkalis are consumed in the recycling process, which is not environmentally friendly and increases the process and cost of treating waste liquids and by-products; third, when using pyrometallurgical recycling, the higher recycling temperature greatly increases the recycling cost and safety issues in the recycling process; fourth, traditional metallurgical recycling methods still exist in the form of single substances or transition metal salts, and if they are to be used as raw materials for the production of electrode materials, a complete industrial process is still required, and the recycling added value is low, which reduces the economic expectations of positive electrode material recycling. Therefore, it is still a considerable challenge to study an efficient recycling method for lithium-ion battery positive electrode materials with more precious metal elements. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for regenerating and upgrading retired ternary lithium-ion batteries in view of the deficiencies of the above-mentioned prior art. The method has great advantages in maximizing the recyclability of metal elements in waste lithium-ion batteries, directly converting waste lithium-ion battery materials into new positive electrode materials, which is more environmentally friendly and economical.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for regenerating and upgrading retired ternary lithium-ion batteries of the present invention, the method is:
[0007] S1, soaking the waste NCM622 soft-pack battery in a 0.5M NaCl solution for 24 hours to obtain the soaked waste NCM622 soft-pack battery;
[0008] S2, dismantling the soaked waste NCM622 soft-pack battery obtained in S1, separating the positive electrode sheet, and cutting it to obtain a rectangular electrode sheet;
[0009] S3, washing the rectangular electrode sheet obtained in S2 with dimethyl carbonate 2 to 3 times to obtain a washed electrode sheet;
[0010] S4, vacuum drying the washed electrode sheet obtained in S3 at a temperature of 110° C. for 3 h to obtain a dried electrode sheet;
[0011] S5, immersing the dried electrode sheet obtained in S4 in a 0.5M NaOH solution and stirring for 2 hours to dissolve the foil current collector to obtain a separated positive electrode material;
[0012] S6, filtering and washing the separated positive electrode material obtained in S5 until the pH value of the filtrate is 7, and then rinsing with anhydrous ethanol for 2 to 3 times, placing the rinsed positive electrode material in a vacuum drying oven at 110° C. and drying for 12 hours to obtain a dried positive electrode material;
[0013] S7, calcining the dried positive electrode material obtained in S6 at a temperature of 650° C. for 5 h, and grinding to obtain a waste positive electrode powder, which is recorded as S-NCM;
[0014] S8, mixing the ternary eutectic molten salt and the S-NCM obtained in S7, and ball milling for 3 h at a rotation speed of 300 r / min to obtain a ball-milled material;
[0015] The ternary eutectic molten salt is LiOH, LiNO in a molar ratio of (1+n):2 / 3×(1+n):1 3 and NiO; wherein n=0.1, 0.2 or 0.3; the molar ratio of S-NCM to NiO is 5:1;
[0016] S9, heating the ball-milled material obtained in S8 from room temperature to 780° C. at a heating rate of 2° C. / min, calcining at a constant temperature for 12 h, and then cooling to room temperature at a cooling rate of 2° C. / min to obtain a calcined material;
[0017] S10. The calcined material obtained in S9 is filtered and washed, and then vacuum dried at 110° C. for 12 h to obtain a positive electrode material, which is recorded as U-NCM.
[0018] Preferably, the rectangular electrode sheet in S2 has a length of 5 cm and a width of 3 cm.
[0019] Preferably, the U-NCM in S10 has a capacity of 190.32 to 199.04 mAh·g at 25°C and 1C rate. -1 The first cycle discharge capacity is 122.03~131.32mAh·g after 200 cycles. -1 , the cycle retention rate is 64.12%~65.97%.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention directly regenerates waste medium-nickel materials (NCM622) into new high-nickel positive electrode materials (NCM811), effectively utilizing the remaining transition metal ions therein, greatly saving production costs, and making waste ternary positive electrode materials have higher added value.
[0022] 2. The traditional positive electrode material recycling methods are mainly divided into wet method and pyrolysis method. The wet method mainly uses acid leaching or alkaline leaching to leach the transition metal ions in the material and recover them in the form of metal elements. The entire recycling process produces a large amount of waste liquid containing acid and alkali, which is costly and does not meet the green and environmentally friendly process requirements; the pyrolysis method mainly recycles by long-term high-temperature calcination. The recycling process releases a large amount of heat, which is costly and not green and environmentally friendly. The present invention mainly adopts the ternary eutectic molten salt method to assist regeneration. The molten salt assisted method is currently a mature production process. Its advantage is that the eutectic molten salt has a low melting point, which can provide a uniform liquid environment for the solid solution reaction, so that the ions have better diffusion ability and promote the reaction. At the same time, the reaction can also be carried out at a relatively low reaction temperature, saving energy consumption.
[0023] 3. The traditional wet regeneration method requires that the metal ions in the waste positive electrode material be leached out with acid or alkali, and then calcined after reprecipitation to obtain the target product. The product obtained by the present invention only needs to be washed and dried, and the subsequent treatment process is simple.
[0024] 4. The present invention aims to utilize the remaining lithium ions and transition metal lithium ions in waste ternary positive electrode materials to convert all waste positive electrode materials into newly generated positive electrode materials, and obtain regenerated high-nickel ternary positive electrode materials, and the regenerated high-nickel ternary positive electrode materials have electrochemical properties similar to those of the commercial positive electrode material NCM811.
[0025] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is an SEM picture of the waste ternary positive electrode material and the regenerated ternary positive electrode material of Example 1 of the present invention.
[0027] Figure 2 3. It is the XRD diagram of the waste ternary positive electrode material and the regenerated ternary positive electrode material of Example 1 of the present invention.
[0028] Figure 3 It is the atomic ratio of the waste ternary positive electrode material and the recycled ternary positive electrode material in Example 1 of the present invention.
[0029] Figure 4 1 is the cyclic voltammetry curve of the waste ternary positive electrode material and the regenerated ternary positive electrode material of Example 1 of the present invention.
[0030] Figure 5 This is a graph showing the electrochemical impedance performance test of the positive electrode material before and after regeneration in Example 1 of the present invention.
[0031] Figure 6 This is a graph showing the electrochemical cycle performance test of the positive electrode material before and after regeneration in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] Example 1
[0033] The method for regenerating and upgrading retired ternary lithium-ion batteries in this embodiment is as follows:
[0034] S1. Soak the used NCM622 soft-pack battery in a 0.5M NaCl solution for 24 hours to achieve complete discharge and avoid fire caused by residual power during disassembly, thereby obtaining the soaked used NCM622 soft-pack battery;
[0035] S2, placing the soaked waste NCM622 soft-pack battery obtained in S1 in a fume hood for disassembly, separating the positive electrode sheet, and cutting to obtain a rectangular electrode sheet with a length of 5 cm and a width of 3 cm;
[0036] S3, washing the rectangular electrode sheet obtained in S2 with dimethyl carbonate (DMC) three times to remove the residual electrolyte on the surface of the electrode sheet, thereby obtaining a washed electrode sheet;
[0037] S4, placing the washed electrode sheet obtained in S3 into a vacuum drying oven, and vacuum drying at a temperature of 110° C. for 3 h to obtain a dried electrode sheet;
[0038] S5, immersing the dried electrode sheet obtained in S4 in a 0.5M NaOH solution and stirring for 2 hours, the aluminum foil current collector is completely dissolved in the NaOH solution, and the positive electrode material and the current collector are completely separated to obtain a separated positive electrode material;
[0039] S6, filtering and washing the separated positive electrode material obtained in S5 until the pH value of the filtrate is 7, and then rinsing with anhydrous ethanol for 3 times, placing the rinsed positive electrode material in a vacuum drying oven at 110° C. and drying for 12 h to obtain a dried positive electrode material;
[0040] S7, calcining the dried positive electrode material obtained in S6 at a temperature of 650° C. for 5 h, in order to remove acetylene black, PVDF and organic impurities mixed in the positive electrode material, and grinding to obtain waste positive electrode powder, which is recorded as S-NCM;
[0041] S8, mixing the ternary eutectic molten salt and the S-NCM obtained in S7, and ball milling them in a ball mill at a rotation speed of 300 r / min for 3 h to obtain a ball-milled material;
[0042] The ternary eutectic molten salt is LiOH, LiNO in a molar ratio of (1+n):2 / 3×(1+n):1 3 and NiO; wherein n=0.1; the molar ratio of S-NCM to NiO is 5:1;
[0043] S9, placing the ball-milled material obtained in S8 into a porcelain boat, heating it from room temperature to 780°C in a tube furnace at a heating rate of 2°C / min, calcining it at a constant temperature for 12 hours, and then cooling it to room temperature at a cooling rate of 2°C / min to obtain a calcined material;
[0044] S10. The calcined material obtained in S9 was filtered and washed, and then vacuum dried at 110° C. for 12 h to obtain a positive electrode material, which was recorded as U-NCM0.1.
[0045] (1) SEM test
[0046] like Figure 1As shown, ab is the SEM images of different scales of the waste ternary positive electrode material, i.e., S-NCM in step S7 of this embodiment, cd is the SEM images of different scales of the regenerated ternary positive electrode material, i.e., U-NCM0.1 prepared in step S10 of this embodiment. From the SEM test results of the waste ternary positive electrode powder and the regenerated ternary powder, it can be seen that the waste ternary positive electrode particles are obviously broken, and a large number of nano-scale small particles are attached to the surface of the particles, which are caused by the particle breakage. After being treated by the process means of the present invention, the cracks on the surface of the particles are restored, and the nano-sized particles on the surface of the material also disappear.
[0047] (2) XRD test
[0048] like Figure 2 As shown in the figure, XRD tests were carried out on the ternary positive electrode powder before and after regeneration. The waste positive electrode material (S-NCM) before regeneration had a serious degree of lithium-nickel mixing, lost the original layered structural characteristics of the material, and the wider peak indicated that the crystallinity of the material gradually decreased; the regenerated positive electrode material (U-NCM0.1) had a typical characteristic peak of a layered structure, corresponding to the R-3m space group, and the thin and narrow characteristic peak indicated that the material had good crystallinity and significantly reduced the degree of lithium-nickel mixing of the material.
[0049] (3)XPS test
[0050] like Figure 3 As shown, XPS tests were performed on the positive electrode materials before and after regeneration. After fitting using Avantage software, the atomic content of each element in the waste positive electrode material was obtained, Li was about 70.92%, Ni was about 58.52%, Co was about 18.93%, and Mn was about 17.67%; the atomic content of each element in the regenerated positive electrode material was about 100.9% Li, about 80.02% Ni, about 10.21% Co, and about 10.04% Mn, which was in line with the stoichiometric ratio of NCM811 positive electrode material.
[0051] (4) Cyclic voltammetry curve test
[0052] Cyclic voltammetry (CV) is a common technique for studying the behavior and rate-determining steps of electrode electrochemical reactions in lithium-ion batteries. In order to determine the reversibility of the material during charge and discharge, the CV was performed at 25 °C and 0.1 mV s -1 The CV curves of the first 5 cycles of the two samples were tested in the voltage range of 2.7-4.3V. Figure 4 As shown. The recycled material has multiple voltage platforms during the charging and discharging process, corresponding to The difference between the oxidation peak and the reduction peak of S-NCM is 0.41V, and the electrode polarization phenomenon is serious. The difference between the oxidation peak and the reduction peak of U-NCM0.1 is 0.225V, and the electrode polarization phenomenon is weakened.
[0053] (5) Electrochemical impedance spectroscopy
[0054] The basic method of electrochemical impedance spectroscopy (EIS) is to apply a small amplitude sinusoidal excitation signal to the system under study and measure its response to obtain an electrochemical impedance spectrum, which is an important method for reflecting electrode interface information and material dynamics. EIS tests were performed on S-NCM and U-NCM0.1, respectively. Figure 5 As shown, it can be seen that the charge transfer impedance of S-NCM is 176Ω, and the charge transfer impedance of U-NCM0.1 is 85.32Ω. After regeneration, the charge transfer impedance is significantly reduced.
[0055] (6) Electrochemical cycle performance test
[0056] like Figure 6 As shown in the figure, the electrochemical performance of the cathode material before and after regeneration was tested. At 25°C and 1.0C rate, the first cycle discharge capacity of S-NCM was 59.18 mAh g -1 After 100 cycles, the discharge capacity is 39.85 mAh g -1 , the capacity retention rate is 67.33%; at 25℃ and 1C rate, the first cycle discharge capacity of U-NCM0.1 is 199.04mAh·g -1 After 200 cycles, the discharge capacity is 131.32 mAh g -1 , the capacity retention rate is 65.97%.
[0057] The regenerated U-NCM prepared in this embodiment has similar electrochemical properties to the commercial positive electrode material NCM811, that is, the NCM622 waste positive electrode material is regenerated and upgraded to the NCM811 positive electrode material.
[0058] This embodiment directly regenerates waste medium-nickel material (NCM622) into new high-nickel positive electrode material (NCM811), effectively utilizing the remaining transition metal ions therein, greatly saving production costs, and making the waste ternary positive electrode material have higher added value.
[0059] Example 2
[0060] The method for regenerating and upgrading retired ternary lithium-ion batteries in this embodiment is as follows:
[0061] S1, soaking the waste NCM622 soft-pack battery in a 0.5M NaCl solution for 24 hours to obtain the soaked waste NCM622 soft-pack battery;
[0062] S2, dismantling the soaked waste NCM622 soft-pack battery obtained in S1, separating the positive electrode sheet, and cutting to obtain a rectangular electrode sheet with a length of 5 cm and a width of 3 cm;
[0063] S3, washing the rectangular electrode sheet obtained in S2 with dimethyl carbonate twice to obtain a washed electrode sheet;
[0064] S4, vacuum drying the washed electrode sheet obtained in S3 at a temperature of 110° C. for 3 h to obtain a dried electrode sheet;
[0065] S5, immersing the dried electrode sheet obtained in S4 in a 0.5M NaOH solution and stirring for 2 hours to dissolve the foil current collector to obtain a separated positive electrode material;
[0066] S6, filtering and washing the separated positive electrode material obtained in S5 until the pH value of the filtrate is 7, and then rinsing with anhydrous ethanol twice, placing the rinsed positive electrode material in a vacuum drying oven at 110° C. and drying for 12 h to obtain a dried positive electrode material;
[0067] S7, calcining the dried positive electrode material obtained in S6 at a temperature of 650° C. for 5 h, and grinding to obtain a waste positive electrode powder, which is recorded as S-NCM;
[0068] S8, mixing the ternary eutectic molten salt and the S-NCM obtained in S7, and ball milling for 3 h at a rotation speed of 300 r / min to obtain a ball-milled material;
[0069] The ternary eutectic molten salt is LiOH, LiNO in a molar ratio of (1+n):2 / 3×(1+n):1 3 and NiO; wherein n=0.2; the molar ratio of the S-NCM to NiO is 5:1;
[0070] S9, heating the ball-milled material obtained in S8 from room temperature to 780° C. at a heating rate of 2° C. / min, calcining at a constant temperature for 12 h, and then cooling to room temperature at a cooling rate of 2° C. / min to obtain a calcined material;
[0071] S10. The calcined material obtained in S9 was filtered and washed, and then vacuum dried at 110° C. for 12 h to obtain a positive electrode material, which was recorded as U-NCM0.2.
[0072] The electrochemical performance of the obtained U-NCM0.2 sample was tested, and it had a conductivity of 196.54 mAh g at 25 °C and 1C rate. -1 The first cycle discharge capacity is 127.14 mAh g after 200 cycles. -1 , the cycle retention rate is 64.69%.
[0073] Example 3
[0074] The method for regenerating and upgrading retired ternary lithium-ion batteries in this embodiment is as follows:
[0075] S1, soaking the waste NCM622 soft-pack battery in a 0.5M NaCl solution for 24 hours to obtain the soaked waste NCM622 soft-pack battery;
[0076] S2, dismantling the soaked waste NCM622 soft-pack battery obtained in S1, separating the positive electrode sheet, and cutting to obtain a rectangular electrode sheet with a length of 5 cm and a width of 3 cm;
[0077] S3, washing the rectangular electrode sheet obtained in S2 with dimethyl carbonate three times to obtain a washed electrode sheet;
[0078] S4, vacuum drying the washed electrode sheet obtained in S3 at a temperature of 110° C. for 3 h to obtain a dried electrode sheet;
[0079] S5, immersing the dried electrode sheet obtained in S4 in a 0.5M NaOH solution and stirring for 2 hours to dissolve the foil current collector to obtain a separated positive electrode material;
[0080] S6, filtering and washing the separated positive electrode material obtained in S5 until the pH value of the filtrate is 7, and then rinsing with anhydrous ethanol for 3 times, placing the rinsed positive electrode material in a vacuum drying oven at 110° C. and drying for 12 h to obtain a dried positive electrode material;
[0081] S7, calcining the dried positive electrode material obtained in S6 at a temperature of 650° C. for 5 h, and grinding to obtain a waste positive electrode powder, which is recorded as S-NCM;
[0082] S8, mixing the ternary eutectic molten salt and the S-NCM obtained in S7, and ball milling for 3 h at a rotation speed of 300 r / min to obtain a ball-milled material;
[0083] The ternary eutectic molten salt is LiOH, LiNO in a molar ratio of (1+n):2 / 3×(1+n):1 3 and NiO; wherein n=0.3; the molar ratio of the S-NCM to NiO is 5:1;
[0084] S9, heating the ball-milled material obtained in S8 from room temperature to 780° C. at a heating rate of 2° C. / min, calcining at a constant temperature for 12 h, and then cooling to room temperature at a cooling rate of 2° C. / min to obtain a calcined material;
[0085] S10. The calcined material obtained in S9 was filtered and washed, and then vacuum dried at 110° C. for 12 h to obtain a positive electrode material, which was recorded as U-NCM0.3.
[0086] The electrochemical performance of the obtained U-NCM0.3 sample was tested, and it had a conductivity of 190.32 mAh g at 25 °C and 1C rate. -1 The first cycle discharge capacity is 122.03 mAh g after 200 cycles. -1 , the cycle retention rate is 64.12%.
[0087] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for regenerating and upgrading retired ternary lithium-ion batteries, characterized in that: The method is: S1, soaking the waste NCM622 soft-pack battery in a 0.5M NaCl solution for 24 hours to obtain the soaked waste NCM622 soft-pack battery; S2, dismantling the soaked waste NCM622 soft-pack battery obtained in S1, separating the positive electrode sheet, and cutting it to obtain a rectangular electrode sheet; S3, washing the rectangular electrode sheet obtained in S2 with dimethyl carbonate 2 to 3 times to obtain a washed electrode sheet; S4, vacuum drying the washed electrode sheet obtained in S3 at a temperature of 110° C. for 3 h to obtain a dried electrode sheet; S5, immersing the dried electrode sheet obtained in S4 in a 0.5M NaOH solution and stirring for 2 hours to dissolve the foil current collector to obtain a separated positive electrode material; S6, filtering and washing the separated positive electrode material obtained in S5 until the pH value of the filtrate is 7, and then rinsing with anhydrous ethanol for 2 to 3 times, placing the rinsed positive electrode material in a vacuum drying oven at 110° C. and drying for 12 hours to obtain a dried positive electrode material; S7, calcining the dried positive electrode material obtained in S6 at a temperature of 650° C. for 5 h, and grinding to obtain a waste positive electrode powder, which is recorded as S-NCM; S8, mixing the ternary eutectic molten salt and the S-NCM obtained in S7, and ball milling them at a rotation speed of 300 r / min for 3 h to obtain a ball-milled material; The ternary eutectic molten salt is a mixture of LiOH, LiNO3 and NiO in a molar ratio of (1+n):2 / 3×(1+n):1; wherein n=0.1, 0.2 or 0.3; and the molar ratio of S-NCM to NiO is 5:1; S9, heating the ball-milled material obtained in S8 from room temperature to 780° C. at a heating rate of 2° C. / min, calcining at a constant temperature for 12 h, and then cooling to room temperature at a cooling rate of 2° C. / min to obtain a calcined material; S10. The calcined material obtained in S9 is filtered and washed, and then vacuum dried at 110° C. for 12 h to obtain a positive electrode material, which is recorded as U-NCM.
2. The method for regenerating and upgrading retired ternary lithium-ion batteries according to claim 1, characterized in that: The rectangular electrode sheet in S2 has a length of 5 cm and a width of 3 cm.
3. The method for regenerating and upgrading retired ternary lithium-ion batteries according to claim 1, characterized in that: The U-NCM described in S10 has a capacity of 190.32 to 199.04 mAh·g at 25°C and 1C rate. -1 The first cycle discharge capacity is 122.03~131.32mAh·g after 200 cycles. -1 , the cycle retention rate is 64.12%~65.97%.